The Effectiveness of Ramadan Focused Education on Awareness and Glycemic Control of Diabetic Muslims (Type 2 Diabetes) During Ramadan Fasting. - Chonlakan Prataksitorn; Phechnoy Singchungchai (Universiti Kebangsaan Malaysia, 2014)
The majority of Muslim diabetic patients are unaware of complications during fasting, therefore diabetic patients who want to fast need a pre–Ramadan assessment and education to increase their awareness of the risks of fasting. This study examined the effectiveness of Ramadan focused education aimed at increasingself-awareness and glycemic control in Muslims with type 2 diabetes who fast during Ramadan.